2014
DOI: 10.1002/2014jc010307
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between coral distributions and physical variables in Amitori Bay, Iriomote Island, Japan

Abstract: The relationship between coral distributions and physical variables was investigated in Amitori Bay, Iriomote Island, Japan. Field observations were conducted to obtain data on coral distributions, sea temperature, sea salinity, wind speed, and river flow rate. The observed data were then used in ocean and wave model numerical simulations and soil particle tracking analysis to obtain the spatial and temporal distributions of wave height and the numbers of soil particles. The main results of this study indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(54 citation statements)
references
References 28 publications
(29 reference statements)
0
54
0
Order By: Relevance
“…Therefore, the CCM is suitable for calculating ocean currents in regions such as the Sakiyama and Amitori bays, which have a large bathymetric gradient ranging from a few meters depth for the coral reefs to 70-m depth for the ocean bottom floor. In fact, previous studies showed that the CCM can reproduce the observations with high precision in Amitori bay (Shimokawa et al 2014b; see Appendix 2) and also other areas (Murakami et al 2015c). In addition, the CCM can support accurate calculation of the inflow rates of freshwater Fig.…”
Section: Numerical Model and Methodsmentioning
confidence: 88%
See 4 more Smart Citations
“…Therefore, the CCM is suitable for calculating ocean currents in regions such as the Sakiyama and Amitori bays, which have a large bathymetric gradient ranging from a few meters depth for the coral reefs to 70-m depth for the ocean bottom floor. In fact, previous studies showed that the CCM can reproduce the observations with high precision in Amitori bay (Shimokawa et al 2014b; see Appendix 2) and also other areas (Murakami et al 2015c). In addition, the CCM can support accurate calculation of the inflow rates of freshwater Fig.…”
Section: Numerical Model and Methodsmentioning
confidence: 88%
“…These features are explainable mainly by seasonal differences in wind speed and direction, but the combination among seasonal differences in wind speed and direction, wind-driven current and topography is also important for them. For Amitori bay, we have conducted studies on the soil particle impact on coastal marine ecosystems such as corals (e.g., Murakami et al 2012;Shimokawa et al 2014bShimokawa et al , 2015Shimokawa et al , 2016Ukai et al 2015) and E. acoroides (e.g., Murakami et al 2014Murakami et al , 2015aNakase et al 2015Nakase et al , 2016. Those results provide the basic information about whether the control of soil input from the rivers should be done or not and how much it should be done.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations